WASP-3b: a strongly irradiated transiting gas-giant planet - Pollacco, D; Skillen, I; Cameron, A; Loeillet, B; Stempels, H; Bouchy, F; Gibson, N; Hebb, L; Hebrard, G; Joshi, Y; McDonald, I; Smalley, B; et al. (2008)
We report the discovery of WASP-3b, the third transiting exoplanet to be discovered by the WASP and SOPHIE collaboration. WASP-3b transits its host star USNO-B1.0 1256-0285133 every 1.846 834 ± 0.000 002 d. Our high-precision radial velocity measurements present a variation with amplitude characteristic of a planetary-mass companion and in phase with the light curve. Adaptive optics imaging shows no evidence for nearby stellar companions, and line-bisector analysis excludes faint, unresolved binarity and stellar activity as the cause of the radial velocity variations. We make a preliminary spectroscopic analysis of the host star and find it to have Teff = 6400 ± 100 K and log g = 4.25 ± 0.05 which suggests it is most likely an unevolved main-sequence star of spectral type F7-8V. Our simultaneous modelling of the transit photometry and reflex motion of the host leads us to derive a mass of 1.76+0.08-0.14 MJ and radius 1.31 +0.07-0.14 RJ for WASP-3b. The proximity and relative temperature of the host star suggests that WASP-3b is one of the hottest exoplanets known, and thus has the potential to place stringent constraints on exoplanet atmospheric models. © 2008 RAS.